Systematic Review on Hospital Efforts to Maintain and Enhance Nurse Competence Worldwide - Arief Yanto; Menik Kustriyani (South East Asia Nursing Research)
Nurses play a pivotal role in delivering high-quality healthcare globally. With the increasing complexity of healthcare systems, maintaining and enhancing nurse competence is essential to ensure patient safety, improve care outcomes, and adapt to technological advancements. This systematic review aims to synthesize recent evidence on hospital-based strategies and interventions implemented worldwide to sustain and improve nurse competence. A comprehensive literature search was conducted across multiple databases for peer-reviewed articles published between 2020 and 2025. Studies focusing on hospital initiatives for nurse competence development were included. Data extraction emphasized study design, intervention types, measured outcomes, and program effectiveness. The review identified several key approaches, including continuing professional development (CPD), simulation-based training, mentorship programs, competency assessment frameworks, digital learning platforms, and interprofessional collaboration initiatives. Evidence indicates that multifaceted strategies combining education, practical training, feedback mechanisms, and organizational support significantly enhance nurses’ clinical skills and confidence. Hospitals worldwide employ diverse yet complementary methods to maintain nursing competence amid evolving healthcare demands. Prioritizing structured CPD programs integrated with innovative teaching methods can optimize nurse performance. Future research should focus on the long-term impact of these interventions across varied cultural contexts.